Pasteurella canis infection in a non‐human primate black‐tailed marmoset (Mico melanurus)—A case report. Issue 2 (5th December 2019) - da Silva, Mayara Inácio Vincenzi; Bento, Heitor José; Maruyama, Fernanda Harumi; Rosa, Janaína Marcela Assunção; Mesquita, Mayara Carvalho de Sousa Rocha; Pavelegini, Lucas Avelino Dandolini; Morgado, Thaís Oliveira; Colodel, Edson Moleta; Nakazato, Luciano; Dutra, Valéria
Abstract: This study reports the pathological and microbiological findings of pneumonia in a Mico melanurus caused by Pasteurella canis, confirmed for molecular analyses. It demonstrated the importance that wild species represent in the epidemiology of pasteurellosis in anthropic environments, when inserted into urban areas.